Interactive Emulator System to Aid Clinical Practice Outcomes for Nurses - Bowtell, Les; Kist, Alexander A.; Osbourne, Daniel; Parker, Victoria R. (International Journal of Online and Biomedical Engineering (iJOE), 2013)
Clinical practice is a key element of nursing studies programmes. Amongst its aims are familiarisation with medical equipment, appropriate use of clinical reasoning in a ward setting and calculation and delivery of patient medication fluids requirements. The setting for this is typically a simulated ward environment and is structured around group training. While this is cost effective, it does not cater well for minority groups and those wishing to train at their own pace. A number of group dynamic related social issues can also lead to students dominating others within the session. This can result in less than satisfactory learning outcomes for the remainder of the group. Other factors that come into play are the wide age range, social and ethnic backgrounds of the nursing student cohort. Recent Remote Access Nursing Laboratory work has shown a marked improvement in residential school assessment results in areas such as readiness to practice and clinical reasoning levels demonstrated for those students in the trial nursing RAL project. With the aim of further enhancing the effectiveness and at the same time reducing implementation costs an interactive IV pump emulator was developed. Enhancements included guided introductions, provision of additional scaffolding and inbuilt annotated assessments. This paper discusses the techniques used and general implementation of this system and reports on positive results of the conducted trials.